2021
DOI: 10.3389/fchem.2021.666867
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Sorting Methods of High-Throughput Droplet-Based Microfluidics in Enzyme Directed Evolution

Abstract: Droplet-based microfluidics has been widely applied in enzyme directed evolution (DE), in either cell or cell-free system, due to its low cost and high throughput. As the isolation principles are based on the labeled or label-free characteristics in the droplets, sorting method contributes mostly to the efficiency of the whole system. Fluorescence-activated droplet sorting (FADS) is the mostly applied labeled method but faces challenges of target enzyme scope. Label-free sorting methods show potential to great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…So called optofluidic devices offer a way to synergistically combine key microfluidics sample processing capabilities with optical functionality, opening up promising avenues for bio- and chemical-sensing 14 . Established optical techniques such as fluorescence-activated droplet sorting 15 , 16 , optical microscopy 17 , 18 , or laser-induced fluorescence (LIF) 19 21 , can be incorporated into microfluidic chips.…”
Section: Introductionmentioning
confidence: 99%
“…So called optofluidic devices offer a way to synergistically combine key microfluidics sample processing capabilities with optical functionality, opening up promising avenues for bio- and chemical-sensing 14 . Established optical techniques such as fluorescence-activated droplet sorting 15 , 16 , optical microscopy 17 , 18 , or laser-induced fluorescence (LIF) 19 21 , can be incorporated into microfluidic chips.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet microfluidics has been widely applied in the discovery and directed evolution of enzymes because of its low cost and high throughput. 44 Microbial cells and enzymes with the desired activities have been isolated based on the characteristics of the microdroplets, such as fluorescence, 9,11 absorbance, 14,15 Raman scattering, 16 electrochemical detection, 17,18 and mass spectrometry. 19,20 In this study, we demonstrated that enzymatic hydrolysis of agarose can be assayed in microdroplets based on their deformability (Figures 3 and 4).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Fluorescence Activated Droplet Sorting (FADS) is a technique that enables the selection of W/O droplets based on the fluorescent signals emitted by the droplet contents as they travel through microchannels. 20 It is a high-throughput methodology that has been used for selecting enzyme mutants with higher activity in directed evolution projects [21][22][23] The technique has also been modified for label-free droplet detection. 24 In microbial interaction studies, FADS has been used to analyze the diversity of antibiotic-producing bacteria from different natural habitats.…”
Section: Introductionmentioning
confidence: 99%